Opportunities to improve detection of genetic predisposition for ovarian cancer applying the Tumor-First workflow - Vera M. Witjes; Joanne A. de Hullu; Angela van Remortele; Lilian Vreede; Michiel Simons; Nicoline Hoogerbrugge; Marjolijn J. L. Ligtenberg (Familial Cancer, 2026)
Genetic testing in ovarian carcinoma (OC) patients is very important for patients and their relatives. The Tumor-First workflow uses a tumor DNA test to stratify germline testing for hereditary cancer predisposition as well as treatment options with PARP inhibitors. This workflow is adopted and successfully implemented nationwide. Here, we evaluated recent tumor DNA testing rates in the Netherlands to identify untested OC patient groups and optimize tumor DNA testing rates. OC patients diagnosed in 2023 or 2024 were selected from the Netherlands Cancer Registry. We analyzed patient characteristics associated with the likelihood of tumor DNA testing using multivariable logistic regression. Tumor-First testing was performed for 1765 out of the 2221 (79%) OC patients. Patients diagnosed with advanced stage OC were more likely to receive tumor DNA testing (OR = 2.5, p < 0.001) than those with low-stage disease. Compared with patients who underwent surgery as primary treatment, those who received chemotherapy or no primary treatment were less likely to be tested (OR = 0.21 and OR = 0.07, respectively, p < 0.001). Patients who died within 100 days were less likely to receive testing (OR = 0.57, p = 0.003). Patients without resection after diagnosis on biopsy/cytology had the lowest Tumor-First testing rates (58% vs. 87–95%, χ2 p < 0.001). Tumor-First testing rates are high. However, OC patients that do not undergo a resection are less likely to undergo testing. With these data strategies to identify hereditary cancer predisposition in patients and their relatives can be further improved.

Evidence for successive breaching events by basking sharks Cetorhinus maximus (Lamniformes: Cetorhinidae) - Simon David Berrow; Michiel De Boeck; Ryan Andrew Davies; Fintan Ryan; Richard Collins (Environmental Biology of Fishes, 2025)
Basking sharks were recorded breaching frequently off the coast of Co Clare, Ireland. The frequency and time between breaching events were analysed to determine any patterns in this behaviour. A total of 93 breaches of basking sharks were recorded over a 3-day period in September 2020. The mean number of breaches per hour, during a total observation period of 515 min, ranged from 6.0 to 15.3 with a mean ± SD of 9.2 ± 4.3 breaches per hour. Inter-Breach-Intervals (IBI) ranged from less than 1 min to a maximum of 34 min with a mean value of 5.4 min (median 2.0 min) across all observations. A total of 39.8% of all breaches were recorded within 1 min of the previous breach, whilst 65.6% were made within 5 min. Results suggest one breaching event may act as a trigger for other breaching events.

Environmental and Geographic Conditions on the Breeding Grounds Drive Bergmannian Clines in Nightjars - Aaron A. Skinner; Alicia M. Korpach; Susanne Åkesson; Marja H. Bakermans; Erin M. Bayne; Thomas J. Benson; Giovanni Boano; R. Mark Brigham; Simon S. Christiansen; Greg J. Conway; Christina M. Davy; Ruben Evens; et al. (Journal of Biogeography, 2025)
Aim To evaluate (1) whether three migratory nightjar species (Family Caprimulgidae) adhere to Bergmann's rule, (2) whether environmental factors on the breeding or wintering grounds determine body size, and (3) which mechanistic hypotheses best explain Bergmannian patterns in body size. Location North and South America; Europe and Africa. Taxon Eastern whip‐poor‐will ( Antrostomus vociferus ), Common nighthawk ( Chordeiles minor ) and European nightjar ( Caprimulgus europaeus ). Methods We used GPS tracking and morphometric data to assess competing hypotheses explaining variation in body size for each species, based on their breeding ( n = 3388) and wintering ( n = 189) locations. Results All three species exhibited Bergmannian patterns in body size, providing the first evidence that nightjars conform to Bergmann's rule despite adaptations to severe environmental conditions. Environmental and geographic variables at breeding sites were stronger predictors of body size than wintering‐site variables. Although we found partial support for Bergmann's temperature regulation hypothesis, geographic variables, rather than specific environmental factors, emerged as the strongest predictors of body size variation. Main Conclusions Latitude and longitude correlated strongly with environmental variables and migratory distance; thus, these geographical variables likely encompass many factors that influence body size in nightjars. The present study is among the first to use tracking data from individual birds to understand how environmental pressures across the annual cycle are related to body size. Our findings highlight the critical role of geographic breeding‐ground factors in shaping Bergmannian patterns, offering robust evidence to support nearly two centuries of research since Bergmann's rule was first described in 1847.

Non-serous ovarian cancer in PTEN Hamartoma Tumor Syndrome: additional evidence for increased risk - Ane J. Schei-Andersen; Vera M. Witjes; Janet R. Vos; Arjen R. Mensenkamp; Anne van Altena; Jolanda Schieving; Michiel Simons; Janneke H. M. Schuurs-Hoeijmakers; Muriel A. Adank; Liselotte P. van Hest; Yvette van Ierland; Mirjam de Jong; et al. (Familial Cancer, 2025)
Increased hereditary cancer risk is one of the hallmarks of PTEN Hamartoma Tumor Syndrome (PHTS) which is caused by a pathogenic germline variant in PTEN . Case reports and some cohort studies have described ovarian cancer (OC) in PHTS patients. Previously, we observed an enrichment of non-serous OC in PHTS compared to sporadic cases (3% vs 1%). However, ovarian cancer is currently not considered a PHTS-related cancer. The aim of this study was to describe five PHTS patients with a pathogenic germline variant in PTEN with non-serous OC. Three of the non-serous OCs were mucinous carcinomas (49, 51 and 52 years) and two were malignant germ cell tumors (8 and 15 years) and all were diagnosed before genetic testing and PHTS diagnosis. In addition to OC, the described patients developed other PHTS-related benign and malignant lesions. We provide further evidence that non-serous ovarian cancer, especially mucinous, endometrioid and malignant germ cell tumors should be further investigated as potential PHTS-related cancers.

How can bottom-up citizen science restore public trust in environmental governance and sciences? Recommendations from three case studies - Artemis Skarlatidou; Muki Haklay; Simon Hoyte; Michiel van Oudheusden; Isabel J. Bishop (Environmental Science & Policy, 2024)

Assessing sustainable development pathways for water, food, and energy security in a transboundary river basin - Amanda Palazzo; Taher Kahil; Barbara A. Willaarts; Peter Burek; Michiel van Dijk; Ting Tang; Piotr Magnuszewski; Petr Havlík; Simon Langan; Yoshihide Wada (Environmental Development, 2024)

Farmland biodiversity monitoring through citizen science: A review of existing approaches and future opportunities - Andy Ruck; René van der Wal; Amelia S. C. Hood; Alice L. Mauchline; Simon G. Potts; Michiel F. WallisDeVries; Erik Öckinger (Ambio, 2024)
Biodiversity monitoring in agricultural landscapes is important for assessing the effects of both land use change and activities that influence farmland biodiversity. Despite a considerable increase in citizen science approaches to biodiversity monitoring in recent decades, their potential in farmland-specific contexts has not been systematically examined. This paper therefore provides a comprehensive review of existing citizen science approaches involving biodiversity monitoring on farmland. Using three complementary methods, we identify a range of programmes at least partially covering farmland. From these, we develop a typology of eight programme types, reflecting distinctions in types of data collected and nature of volunteer involvement, and highlight their respective strengths and limitations. While all eight types can make substantial contributions to farmland biodiversity monitoring, there is considerable scope for their further development—particularly through increased engagement of farmers, for whom receiving feedback on the effects of their own practices could help facilitate adaptive management.

Relict stands of Central European oaks: Unravelling autochthony and genetic structure based on a multi-population study - Charalambos Neophytou; Devrim Semizer-Cuming; Hans-Gerhard Michiels; Antoine Kremer; Simon Jansen; Barbara Fussi (Forest Ecology and Management, 2024)

Machine learning techniques to characterize functional traits of plankton from image data - Eric C. Orenstein; Sakina‐Dorothée Ayata; Frédéric Maps; Érica C. Becker; Fabio Benedetti; Tristan Biard; Thibault de Garidel‐Thoron; Jeffrey S. Ellen; Filippo Ferrario; Sarah L. C. Giering; Tamar Guy‐Haim; Laura Hoebeke; et al. (Limnology and Oceanography, 2022)
Plankton imaging systems supported by automated classification and analysis have improved ecologists' ability to observe aquatic ecosystems. Today, we are on the cusp of reliably tracking plankton populations with a suite of lab‐based and in situ tools, collecting imaging data at unprecedentedly fine spatial and temporal scales. But these data have potential well beyond examining the abundances of different taxa; the individual images themselves contain a wealth of information on functional traits. Here, we outline traits that could be measured from image data, suggest machine learning and computer vision approaches to extract functional trait information from the images, and discuss promising avenues for novel studies. The approaches we discuss are data agnostic and are broadly applicable to imagery of other aquatic or terrestrial organisms.

EurOP2E – the European Open Platform for Prescribing Education, a consensus study among clinical pharmacology and therapeutics teachers - Michiel J. Bakkum; Milan C. Richir; Paraskevi Papaioannidou; Robert Likic; Emilio J. Sanz; Thierry Christiaens; João N. Costa; Romaldas Mačiulaitis; Lorena Dima; Jamie Coleman; Jelle Tichelaar; Michiel A. van Agtmael; et al. (European Journal of Clinical Pharmacology, 2021)
Purpose Sharing and developing digital educational resources and open educational resources has been proposed as a way to harmonize and improve clinical pharmacology and therapeutics (CPT) education in European medical schools. Previous research, however, has shown that there are barriers to the adoption and implementation of open educational resources. The aim of this study was to determine perceived opportunities and barriers to the use and creation of open educational resources among European CPT teachers and possible solutions for these barriers. Methods CPT teachers of British and EU medical schools completed an online survey. Opportunities and challenges were identified by thematic analyses and subsequently discussed in an international consensus meeting. Results Data from 99 CPT teachers from 95 medical schools were analysed. Thirty teachers (30.3%) shared or collaboratively produced digital educational resources. All teachers foresaw opportunities in the more active use of open educational resources, including improving the quality of their teaching. The challenges reported were language barriers, local differences, lack of time, technological issues, difficulties with quality management, and copyright restrictions. Practical solutions for these challenges were discussed and include a peer review system, clear indexing, and use of copyright licenses that permit adaptation of resources. Conclusion Key challenges to making greater use of CPT open educational resources are a limited applicability of such resources due to language and local differences and quality concerns. These challenges may be resolved by relatively simple measures, such as allowing adaptation and translation of resources and a peer review system.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

The European Association for Clinical Pharmacology and Therapeutics—25 years’ young and going strong - Jamie J. Coleman; Caroline Samer; Markus Zeitlinger; Michiel van Agtmael; Gerard A. Rongen; Pierre Marquet; Tabassome Simon; Donald Singer; Vangelis G. Manolopoulos; Ylva Böttiger (European Journal of Clinical Pharmacology, 2019)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Species richness declines and biotic homogenisation have slowed down for NW ‐European pollinators and plants - Luísa Gigante Carvalheiro; William E. Kunin; Petr Keil; Jesus Aguirre‐Gutiérrez; Willem Nicolaas Ellis; Richard Fox; Quentin Groom; Stephan Hennekens; Wouter Van Landuyt; Dirk Maes; Frank Van de Meutter; Denis Michez; et al. (Ecology Letters, 2013)
Concern about biodiversity loss has led to increased public investment in conservation. Whereas there is a widespread perception that such initiatives have been unsuccessful, there are few quantitative tests of this perception. Here, we evaluate whether rates of biodiversity change have altered in recent decades in three European countries (Great Britain, Netherlands and Belgium) for plants and flower visiting insects. We compared four 20‐year periods, comparing periods of rapid land‐use intensification and natural habitat loss (1930–1990) with a period of increased conservation investment (post‐1990). We found that extensive species richness loss and biotic homogenisation occurred before 1990, whereas these negative trends became substantially less accentuated during recent decades, being partially reversed for certain taxa (e.g. bees in Great Britain and Netherlands). These results highlight the potential to maintain or even restore current species assemblages (which despite past extinctions are still of great conservation value), at least in regions where large‐scale land‐use intensification and natural habitat loss has ceased.